Touch Therapy Or Light Massage That Stimulates The Body To Release Endorphine Compounds (Endorphine Massage) For Labor In Mothers In Active Phase Of In-Partu With Pain In The First And Second Periods - Darwis, Amelia; Wahyuni, Sri; Syahridayanti, Syahridayanti; Pratiwi, Cici (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The importance of Endorphin Massage lies in its ability to address various aspects of labor. The purpose of this study was to find the effect of endorphin massage on pain in the first and second stages of active labor in inpartu mothers at the Palopo Health Center. The method used was a Quasy Experiment with a Nonequivalent Control Group Design, which is a type of research that observes population data or samples only once at the same time. The population in this study were all mothers who gave birth normally and the sample in this study was some of the mothers who gave birth at the Palopo Health Center as many as 8 people, of which 4 people were given Endorphin massage and 4 people were not given Endorphine massage with this research sampling carried out in a way Purposive Sampling And use Independent test Sample Test. The results of the study showed that the difference in average pain intensity in the pre-test and post-test in pregnant women was 1.137 with a p-value of 0.000 (<0.05) meaning that there was a difference in average pain intensity before and after being given endorphin massage treatment for 3 consecutive days. The conclusion is that endorphin massage is not painful and prevents the sensation of pain from traveling to the central nervous system. Therefore, stimulation is carried out in a harmless way and is able to suppress pain.